The Traditional Games of Serbia - Aksić, Nina V. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
This paper presents a short review of the traditional games that used to be played and that are still played in Serbia. The comparative analysis of the traditional games shows that certain games are played in the entire country, others are played in close or adjacent regions, whereas some originate and are played in one region only. This review of the traditional games of Serbia represents a basis for the future work, since there is enough material indicating that it should be conducted more extensively and more thoroughly, as well as grounded in a comprehensive collection of data and an in-depth field research.
Keywords: development and transformation of games; geographical affiliation; way of playing; Serbia; traditional games